Challenges to the Reforestation Pipeline in the United States - Fargione, Joseph; Haase, Diane L.; Burney, Owen T.; Kildisheva, Olga A.; Edge, Greg; Cook-Patton, Susan C.; Chapman, Teresa; Rempel, Austin; Hurteau, Matthew D.; Davis, Kimberley T.; Dobrowski, Solomon; Enebak, Scott; et al. (Frontiers in Forests and Global Change, 2021)
Large-scale global reforestation goals have been proposed to help mitigate climate change and provide other ecosystem services. To explore reforestation potential in the United States, we used GIS analyses, surveys of nursery managers and foresters, and literature synthesis to assess the opportunities and challenges associated with meeting proposed reforestation goals. We considered a scenario where 26 million hectares (64 million acres) of natural and agricultural lands are reforested by 2040 with 30 billion trees at an estimated cost of $33 ($24–$53) billion USD. Cost per hectare will vary by region, site conditions, and other factors. This scenario would require increasing the number of tree seedlings produced each year by 1.7 billion, a 2.3-fold increase over current nursery production levels. Additional investment (not included in the reforestation cost estimate) will be needed to expand capacity for seed collection, seedling production, workforce development, and improvements in pre- and post-planting practices. Achieving this scenario will require public support for investing in these activities and incentives for landowners.